Inspiring a fractal approach in distributed healthcare information systems: A review - Ahmed, N.S.; Yasin, N.M. (Academic Journals, 2010)
The structure of healthcare information systems (HISs) need flexibility to overcome modifications and maintain system requirements, such as quickly and accurately circulating and updating productive information among system units. This paper proposes the incorporation of fractal features in HISs. Fractal features can provide many solutions to improve the flexibility and quick adaptability of the system to environmental changes. The fractal theory, its features and its implementations are reviewed in this paper to investigate the possibility of developing cooperative HISs based on fractal theory. This paper proposes an integrated cooperative HIS conceptual framework to explain the roles of fractal features in improving the flexibility and adaptability of the HIS. This research includes a survey conducted in two healthcare centers in North Iraq. The survey shows the necessity of fractal-based HIS to improve the cooperation among system units.